Sri Lanka : Third Post-Program Monitoring Discussion-Staff Report; Press Release; and Statement by the Executive Director for Sri Lanka. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper focuses on Sri Lanka's Third Post-Program Monitoring Discussion. Sri Lanka's recent macroeconomic performance has generally been strong but risks appear to be on the rise. Real GDP growth registered 7.4 percent in 2014. Growth was broad-based, with the exception of agriculture, which suffered from drought early in the year and heavy rains and flooding in the fourth quarter. Price pressures have been contained, with headline and core inflation declining to 2.1 and 1.2 percent, respectively, by end-year. The outlook is broadly stable but set against heightened downside risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet